Cement-stabilized phosphogypsum-stone chips mixture and preparation method thereof
Through the preparation of cement-stabilized phosphogypsum-stone chip mixture, the modification treatment process is used to convert industrial waste into high-performance building materials, solving the problems of high cost of traditional cement materials and environmental pollution, and realizing resource recycling and performance improvement .
Patent Information
- Application Number
- CN202411302894.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The raw materials are costly and have a great impact on the environment during the preparation of traditional cement-stabilized materials. It is difficult for the existing technology to effectively utilize industrial waste phosphogypsum and stone chips, resulting in waste of resources and environmental pollution.
Using cement-stabilized phosphogypsum-stone chip mixture, the phosphogypsum, stone chips, graded particle size fly ash, modified steel slag powder, ore powder, sodium hydroxide and composite modification through specific proportioning and modification treatment processes. The fibers are prepared by mechanical stirring to form high-performance building materials.
It realizes the resource utilization of industrial solid waste, reduces the production cost of building materials, meets the strength requirements of semi-rigid base materials of high-grade highways, improves crack resistance, extends the service life of the road, and reduces environmental damage.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste admixture preparation, and in particular to a cement-stabilized phosphogypsum-stone chip mixture and a preparation method thereof. Background Art
[0002] Phosphogypsum and stone chips are common solid wastes in industrial production. Large amounts of accumulation not only occupy land, but also may pollute the environment. Therefore, how to effectively utilize these wastes and realize their resource utilization is an important topic in the current field of building materials technology.
[0003] As a common building material, cement stabilized materials have stable performance and convenient construction, and are widely used in engineering fields such as roads, bridges, and buildings. However, in the preparation process of traditional cement stabilized materials, the cost of raw materials is high and the impact on the environment is large. Therefore, adding solid waste materials such as phosphogypsum and stone chips to cement stabilized materials to reduce raw material costs and reduce pollution and waste is a major direction of research and development of construction materials at this stage. On this basis, the addition of solid waste materials must also ensure the mechanical properties of the final material. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a cement-stabilized phosphogypsum-stone chip mixture and a preparation method thereof, which can recycle industrial waste and reduce the production cost of building materials, while effectively ensuring the mechanical properties of building materials.
[0005] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0006] A cement-stabilized phosphogypsum-stone chip mixture, characterized in that the mixture is composed of the following materials in parts by weight: 40-80 parts of phosphogypsum, 40-80 parts of stone chips, 3-7 parts of cement, 5-15 parts of fly ash with graded particle size, 5-15 parts of modified steel slag powder, 5-20 parts of mineral powder, 1-3 parts of sodium hydroxide, 1-3 parts of composite modified fiber, and 6-10 parts of water;
[0007] The modified steel slag powder is prepared by acid-washing the steel slag powder, mixing it with a coupling agent, and performing surface treatment. The preparation method of the modified steel slag powder comprises the following steps:
[0008] S1-1, adding steel slag powder to clean water for dispersion, adjusting the pH to 4.5-5, acid leaching for 30-40 minutes, adjusting the pH to neutral, filtering and drying, and obtaining pretreated steel slag powder for use;
[0009] S1-2, placing the above-mentioned pretreated steel slag powder in water, adding a silane coupling agent, stirring and mixing evenly, filtering and drying, and then mixing with an aluminate coupling agent in a high-speed mixer to obtain modified steel slag powder, wherein the amount of the silane coupling agent added is 0.3%-0.5% of the total mass of the pretreated steel slag powder, and the amount of the aluminate coupling agent added is 0.5%-0.8% of the total mass of the pretreated steel slag powder;
[0010] The composite modified fiber is obtained by modifying plant fiber and blending it with polypropylene fiber, and the preparation method of the composite modified fiber includes the following steps:
[0011] S2-1, soaking the plant fiber in a solution with a pH of 4-4.5 for 20 minutes, then rinsing with water for 3-5 times, and then performing steam explosion treatment to obtain the modified plant fiber for standby use, wherein the steam explosion treatment is performed at a high temperature of 121° C. for 20-30 seconds;
[0012] S2-2, mixing the modified plant fiber and the polypropylene fiber in equal amounts to obtain a composite modified fiber.
[0013] Preferably, the cement is any one of P·0 42.5, P·F 32.5, P·F 42.5, P·C 32.5, and P·C 42.5.
[0014] Preferably, in the graded particle size fly ash, fly ash with a particle size distribution of 200-300 μm accounts for 15%-30% of the total amount, fly ash with a particle size distribution of 80-150 μm accounts for 40%-50% of the total amount, and the remaining fly ash has a particle size range of <45 μm.
[0015] The preparation method of cement-stabilized phosphogypsum-stone chips mixture comprises the following steps:
[0016] (1) Weigh phosphogypsum, stone chips, cement, fly ash of graded particle size, modified steel slag powder, mineral powder, sodium hydroxide and composite modified fiber according to the proportion;
[0017] (2) Mechanically stir and mix the modified steel slag powder and the composite modified fiber, then add phosphogypsum, stone chips, cement, fly ash with graded particle sizes, and mineral powder, and continue to mechanically stir to obtain a uniform mixture for use;
[0018] (3) Place sodium hydroxide in a container with a certain amount of water and stir to dissolve evenly to obtain a sodium hydroxide solution for later use;
[0019] (4) Pour the sodium hydroxide solution into the above mixture and stir thoroughly again to obtain a cement-stabilized phosphogypsum-stone chip mixture.
[0020] Preferably, in the step (1), the speed of mechanical stirring and mixing of the modified steel slag powder and the composite modified fiber is 800-1000 r / min, and the stirring time is 10-15 min. The subsequent addition of phosphogypsum, stone chips, cement, fly ash with graded particle size, and mineral powder and continued mechanical stirring is at a speed of 200-400 r / min, and the stirring time is 40-60 min.
[0021] The present invention provides a cement-stabilized phosphogypsum-stone chip mixture and a preparation method thereof, which has the following advantages over the prior art:
[0022] (1) The mixture prepared by the present invention meets the strength requirements of the semi-rigid base material of high-grade highways in the current specifications, and takes into account the good anti-cracking effect of the material, providing a high-performance and economically feasible solution for engineering fields such as construction and roads;
[0023] (2) The present invention not only focuses on improving the performance of the mixture, but also is committed to the resource utilization of industrial solid waste. Components such as phosphogypsum, stone chips, fly ash with graded particle sizes and modified steel slag powder are all derived from industrial by-products. These solid wastes can be converted into cement-stabilized phosphogypsum-stone chips mixture by direct use or use after treatment, and then scientifically and reasonably proportioned and prepared. This not only reduces the damage of industrial solid waste to the environment, but also realizes the recycling of resources, making a positive contribution to environmental protection and sustainable development.
[0024] (3) The mixture prepared by the present invention has good mechanical properties and shrinkage, and can be used in the road field to effectively improve the crack resistance of the road surface and extend the service life of the road. The mixture can also be used in other engineering fields such as bridges and buildings to achieve good application effects. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The following phosphogypsum is an industrial by-product of wet-process phosphoric acid preparation, and the content ratio of its main components is shown in Table 1 below:
[0027] Table 1
[0028]
[0029] Stone chips are the waste screened out from the production of crushed stone in the slag plant. The content of the main components is shown in Table 2 below:
[0030] Table 2
[0031]
[0032] The specific surface area of steel slag powder is 400m 2 / kg-600m 2 / kg of ground steel slag powder, the main component content is shown in Table 3 below:
[0033] Table 3
[0034]
[0035] The content ratio of the main components of fly ash is shown in Table 4 below:
[0036] Table 4
[0037]
[0038] The mineral powder is S95 blast furnace slag powder;
[0039] The length of polypropylene fiber is 1-1.25cm;
[0040] The plant fiber is ramie fiber, with a length of 1-1.25 cm;
[0041] The silane coupling agent is silane coupling agent KH-550;
[0042] The aluminate coupling agent is methyl tributylidene oxime silane;
[0043] The cement is Conch P·0 42.5 ordinary Portland cement, with a 28d compressive strength of 49.4MPa and a specific surface area of 350m 2 / kg.
[0044] Embodiment 1:
[0045] 1. Preparation of pretreated raw materials:
[0046] 1. Preparation of modified steel slag powder:
[0047] (1) Add steel slag powder to 5 times the amount of clean water, stir and disperse, then adjust the pH to 4.5, carry out acid leaching for 35 minutes, then adjust the pH to neutral, filter and dry at 60°C to obtain pretreated steel slag powder for use;
[0048] (2) The above-mentioned pretreated steel slag powder is placed in 2 times the volume of clean water, and then 0.4% of the total mass of the pretreated steel slag powder is added with a silane coupling agent, and the mixture is stirred and mixed evenly. The mixture is then filtered and dried at 60°C. After that, the mixture is mixed with 0.6% of the total mass of the pretreated steel slag powder with an aluminate coupling agent, and placed in a high-speed mixer. The mixture is stirred at 85°C and a speed of 800 r / min for 10 minutes to obtain modified steel slag powder.
[0049] 2. Preparation of composite modified fibers:
[0050] (1) The plant fiber is immersed in a solution with a pH of 4 for 20 minutes, then rinsed with water for 4 times, and then subjected to steam explosion treatment at 121°C for 30 seconds to obtain the modified plant fiber for use;
[0051] (2) The modified plant fiber and polypropylene fiber are mixed in equal amounts to obtain a composite modified fiber.
[0052] 3. Preparation of composite fibers:
[0053] The plant fiber and the polypropylene fiber are mixed in equal amounts to obtain a composite fiber.
[0054] 4. Preparation of fly ash:
[0055] Fly ash A: The fly ash particle size is screened, and the fly ash with a particle size distribution of 200-300μm accounts for 15%-30% of the total amount, the fly ash with a particle size distribution of 80-150μm accounts for 40%-50% of the total amount, and the remaining fly ash particle size range is less than 45μm;
[0056] Fly ash B: The particle size of sieved fly ash is 200-300μm;
[0057] Fly ash C: Screened fly ash particle size, fly ash particle size is 80-150μm;
[0058] Fly ash D: Screened fly ash particle size, fly ash particle size <45μm;
[0059] 2. Preparation of cement stabilized phosphogypsum-stone chips mixture:
[0060] 1. Prepare materials according to the following mass ratio:
[0061] 60 parts of phosphogypsum, 60 parts of stone chips, 5 parts of cement, 10 parts of fly ash, 10 parts of steel slag, 12 parts of mineral powder, 2 parts of sodium hydroxide, 2 parts of fiber material, and 8 parts of water.
[0062] 2. Mechanically mix the steel slag and fiber materials at a speed of 900 r / min for 12 minutes, then add phosphogypsum, stone chips, cement, fly ash and mineral powder, and continue to mechanically mix at a speed of 300 r / min for 50 minutes to obtain a mixture for use;
[0063] 3. Stir and dissolve the sodium hydroxide in water evenly to obtain a sodium hydroxide solution for later use;
[0064] 4. Pour the sodium hydroxide solution into the above mixture and stir thoroughly again to obtain a cement-stabilized phosphogypsum-stone chip mixture.
[0065] Referring to the above preparation method, different fly ash, steel slag and fiber materials were selected according to Table 5 below to prepare mixtures of different experimental groups:
[0066] Table 5
[0067]
[0068] Detection:
[0069] 1. After fully stirring the mixtures described in the above experimental groups 1-6, standard specimens were prepared according to the "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG E51-2009), and the unconfined compressive strength and shrinkage coefficient of the specimens were measured. The specific results are shown in Table 6 below:
[0070] Table 6
[0071]
[0072] It can be seen from the above table that the mixture prepared in experimental group 1 has higher unconfined compressive strength and lower shrinkage coefficient, which reduces cracks caused by shrinkage and effectively resists cracking.
[0073] 2. Shear strength test:
[0074] The mixtures described in the above experimental groups 1-6 were fully stirred and loaded into a mold for compaction, and then left to stand for 48 hours for solidification. The solidified gypsum-based construction solid waste admixture was made into a cake-shaped specimen with a diameter of Φ=61.8 mm and h=20 mm. Three parallel specimens were set for each group of specimens. After standing and demoulding, the specimens were wrapped with plastic wrap to remove air and then sealed. They were placed in a curing box at a constant temperature of 20±2℃ and the humidity was controlled to be 90%-95% for curing for 3d, 7d, and 28d, and then taken out. The shear strength test of the specimens was carried out using a ZJ strain-controlled direct shear apparatus (the vertical pressure was set to 300kPa). The specific test results are shown in Table 7 below:
[0075] Table 7
[0076]
[0077] It can be seen from the above table that the mixture prepared in experimental group 1 has better shear strength and is suitable for use as a building material.
[0078] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cement-stabilized phosphogypsum-stone chip mixture, It is characterized in that The mixture is composed of the following materials in parts by weight: 40-80 parts of phosphogypsum, 40-80 parts of stone chips, 3-7 parts of cement, 5-15 parts of fly ash with graded particle size, 5-15 parts of modified steel slag powder, 5-20 parts of mineral powder, 1-3 parts of sodium hydroxide, 1-3 parts of composite modified fiber, and 6-10 parts of water; among the fly ash with graded particle size, the fly ash with a particle size distribution of 200-300 μm accounts for 15%-30% of the total amount, the fly ash with a particle size of 80-150 μm accounts for 40%-50% of the total amount, and the particle size range of the remaining fly ash is less than 45 μm; The modified steel slag powder is prepared by acid-washing the steel slag powder, mixing it with a coupling agent, and performing surface treatment. The preparation method of the modified steel slag powder comprises the following steps: S1-1, adding steel slag powder to clean water for dispersion, adjusting the pH to 4.5-5, performing acid leaching for 30-40 minutes, adjusting the pH to neutral, filtering and drying, and obtaining pretreated steel slag powder for use; S1-2, placing the above-mentioned pretreated steel slag powder in water, adding a silane coupling agent, stirring and mixing evenly, filtering and drying, and then mixing with an aluminate coupling agent in a high-speed mixer to obtain modified steel slag powder, wherein the amount of the silane coupling agent added is 0.3%-0.5% of the total mass of the pretreated steel slag powder, and the amount of the aluminate coupling agent added is 0.5%-0.8% of the total mass of the pretreated steel slag powder; The composite modified fiber is obtained by modifying plant fiber and blending it with polypropylene fiber, and the preparation method of the composite modified fiber includes the following steps: S2-1, soaking the plant fiber in a solution with a pH of 4-4.5 for 20 minutes, then rinsing with water for 3-5 times, and then performing steam explosion treatment to obtain the modified plant fiber for standby use, wherein the steam explosion treatment is performed at a high temperature of 121° C. for 20-30 seconds; S2-2, mixing the modified plant fiber and the polypropylene fiber in equal amounts to obtain a composite modified fiber.
2. A cement-stabilized phosphogypsum-stone chip mixture according to claim 1, Features: The cement is any one of P·0 42.5, P·F 32.5, P·F 42.5, P·C 32.5, and P·C 42.
5.
3. A method for preparing a cement-stabilized phosphogypsum-stone chip mixture as claimed in any one of claims 1 to 2, It is characterized in that The preparation method comprises the following steps: (1) Weigh phosphogypsum, stone chips, cement, fly ash of graded particle size, modified steel slag powder, mineral powder, sodium hydroxide and composite modified fiber according to the proportion; (2) Mechanically stir and mix the modified steel slag powder and the composite modified fiber, then add phosphogypsum, stone chips, cement, fly ash with graded particle sizes, and mineral powder, and continue to mechanically stir to obtain a uniform mixture for use; (3) Place sodium hydroxide in a container with a certain amount of water and stir to dissolve evenly to obtain a sodium hydroxide solution for later use; (4) Pour the sodium hydroxide solution into the above mixture and stir thoroughly again to obtain a cement-stabilized phosphogypsum-stone chip mixture.
4. The preparation method according to claim 3, Features: In the step (1), the speed of mechanical stirring and mixing of modified steel slag powder and composite modified fiber is 800-1000r / min, and the stirring time is 10-15min. The speed of mechanical stirring of subsequent addition of phosphogypsum, stone chips, cement, graded particle size fly ash and mineral powder is 200-400r / min, and the stirring time is 40-60min.
